2018
DOI: 10.1161/hypertensionaha.118.10824
|View full text |Cite
|
Sign up to set email alerts
|

Vascular Nox (NADPH Oxidase) Compartmentalization, Protein Hyperoxidation, and Endoplasmic Reticulum Stress Response in Hypertension

Abstract: Vascular Nox (NADPH oxidase)-derived reactive oxygen species and endoplasmic reticulum (ER) stress have been implicated in hypertension. However, relationships between these processes are unclear. We hypothesized that Nox isoforms localize in a subcellular compartment-specific manner, contributing to oxidative and ER stress, which influence the oxidative proteome and vascular function in hypertension. Nox compartmentalization (cell fractionation), O (lucigenin), HO (amplex red), reversible protein oxidation (s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
74
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 91 publications
(84 citation statements)
references
References 44 publications
2
74
1
Order By: Relevance
“…We demonstrated that vascular hypercontractility in stroke-prone spontaneously hypertensive rats (SHR-SPs) involves oxidative and ER stress through Nox4-dependent processes. 18 Inhibition of ER stress with the use of 4-phenylbutyric acid (4-PBA) and STF083010 (an IRE1-XBP1 disruptor) ameliorated vascular dysfunction in SHR-SPs. 18 Treatment of SHRs with 4-PBA reduced blood pressure and improved vascular function and structure by ameliorating ER stress.…”
Section: R Esum Ementioning
confidence: 99%
See 3 more Smart Citations
“…We demonstrated that vascular hypercontractility in stroke-prone spontaneously hypertensive rats (SHR-SPs) involves oxidative and ER stress through Nox4-dependent processes. 18 Inhibition of ER stress with the use of 4-phenylbutyric acid (4-PBA) and STF083010 (an IRE1-XBP1 disruptor) ameliorated vascular dysfunction in SHR-SPs. 18 Treatment of SHRs with 4-PBA reduced blood pressure and improved vascular function and structure by ameliorating ER stress.…”
Section: R Esum Ementioning
confidence: 99%
“…18 Inhibition of ER stress with the use of 4-phenylbutyric acid (4-PBA) and STF083010 (an IRE1-XBP1 disruptor) ameliorated vascular dysfunction in SHR-SPs. 18 Treatment of SHRs with 4-PBA reduced blood pressure and improved vascular function and structure by ameliorating ER stress. 12 Although ERand mitochondria-derived ROS may contribute in part to oxidative stress in hypertension, the upstream driving factor appears to be Nox activation.…”
Section: R Esum Ementioning
confidence: 99%
See 2 more Smart Citations
“…chaperones 4-phenyl butyric acid (4-PBA) and taurineconjugated ursodeoxycholic acid (TUDCA) are approved by US Food and Drug Administration (FDA) for treating urea cycle disorders and biliary cirrhosis respectively. Nox (NADPH-oxidase) subcellular compartmentalization contributes to oxidative and ER stress, resulting in increased proliferation of vascular smooth muscle cells (VSMCs), protein hyperoxidation and vascular dysfunction in hypertension; and 4-PBA attenuates hypercontractility and vascular reactive oxygen species (ROS) formation in the stroke-prone spontaneous hypertensive rats (SHRs) [9]. Oral administration of 4-PBA lowers blood pressure, reduces vasoconstriction and enhances vasodilation in small mesenteric arteries from SHRs through inhibition of ER stress and oxidative stress [10].…”
Section: Introductionmentioning
confidence: 99%